Investment Analysis for Mangrove Ecosystems in the Ayeyarwady Region - World Bank (World Bank, Washington, DC, 2021)
Mangroves provide essential ecosystem functions and services that support coastal communities. Despite their importance, they have been degraded and removed globally resulting in loss of resilience of coastlines, their communities, and economies. Myanmar in particular has suffered from high levels of mangrove loss and has the highest current rate of mangrove loss among mangrove holding nations. The role of mangroves in protecting coastlines and communities from storms and flooding, regulating carbon and nutrient cycles, and supporting fisheries has been well established. Yet, the effects of deforestation have resulted in lowering the capacity of mangrove forests to effectively act as a buffer against waves and storm surges. With the development goal of enhancing economic and environmental conditions, in 2016 the government launched the Myanmar Reforestation and Rehabilitation Program (MRRP 2017- 2026). The MRRP aims to create impact through a shift from degraded forests to better quality forests and income improvement of local communities. This study comprises intensive data collection, including mapping and on-ground assessment of mangrove resources, detailed household surveys on how community members use mangroves and what incomes they receive, accumulation of knowledge of costs for restoration, and management activities by governments and non-government organizations.